2014
DOI: 10.1016/j.yexmp.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Renin angiotensin system modulates mTOR pathway through AT2R in HIVAN

Abstract: Mammalian target of rapamycin (mTOR) has been reported to contribute to the development of HIV-associated nephropathy (HIVAN). We hypothesized that HIV may be activating renal tissue mTOR pathway through renin angiotensin system (RAS) via Angiotensin Receptor Type II receptor (AT2R). Renal tissues of Vpr transgenic and Tg26 (HIVAN) mice displayed enhanced phosphorylation of mTOR and p70S6K. Aliskiren, a renin inhibitor attenuated phosphorylation of both mTOR and p70S6K in renal tissues of HIVAN mice. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This is consistent with a recent clinical study showing that serum renin activities were similar in non-HIV and HIV-infected subjects while on ad libitum sodium diet and were similarly increased by a low sodium diet [38]. HIV enhances Ang II production and renin expression through the vitamin D receptor [39]; the role of vitamin D in the HIV-related renin response to a low sodium diet remains to be determined.…”
Section: Plos Onesupporting
confidence: 90%
“…This is consistent with a recent clinical study showing that serum renin activities were similar in non-HIV and HIV-infected subjects while on ad libitum sodium diet and were similarly increased by a low sodium diet [38]. HIV enhances Ang II production and renin expression through the vitamin D receptor [39]; the role of vitamin D in the HIV-related renin response to a low sodium diet remains to be determined.…”
Section: Plos Onesupporting
confidence: 90%
“…Finally, another pathway that contributes to the development of HIV nephropathy is RAAS-dependent phosphorylation and activation of mTOR. Interestingly, this is blocked by AT2 but not AT1 antagonists, demonstrating the involvement of the putatively “protective” AT2 receptor in the pathogenesis of HIV nephropathy [ 50 ]. In view of all the findings above, it is not surprising that ACE inhibitors [ 51 ] and AT1 receptor blockers [ 52 ] are protective of progressive proteinuria and renal dysfunction in subjects with HIV nephropathy.…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%
“…Thus, inactivation of mTOR is an important protective mechanism underlying the involvement of ALS in the pathological process of cardiac hypertrophy. It was previously reported that the activation of RAS stimulates the mTOR pathway in HIV-associated nephropathy (33). In addition, ALS and valsartan were found to improve metabolic signaling, oxidative stress, and myocardial tissue remodeling, at least partially, through the activation of p-mTOR expression (24).…”
Section: Discussionmentioning
confidence: 94%